The imperatives of challenges for Africa in the knowledge age: status and role of National Information Policy (2011)
In principle, the emergence of National Information Policy (NIP) as a framework for developing information resources and institutions was welcomed by most countries in Africa with a messianic zeal. However, most of these countries, particularly those in the sub-sahara region, were unable to correspondingly match their zeal with concrete efforts aimed at enunciating and implementing the policy. This situation is not unconnected with mitigating factors and certain development peculiarities of some of the countries, which are discussed in this paper. Against the background of the above factors and peculiarities, most countries in the sub-region suddenly found themselves at a crossroads with the emergence of the information society that is typified by the increasing prevalence and convergence of information and communications infrastructure (NICI) initiative is discussed in the wider context of national and regional development objectives. The challenges of the knowledge age are also articulated in the light of the way forward for development in Africa. The paper concludes that the alternative to African countries’ failure to address these challenges will be for them to remain attached to the apron string of donor agencies and countries in perpetuity